PENGARUH PEMAHAMAN WAJIB PAJAK, KESADARAN WAJIB PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI YANG MELAKUKAN KEGIATAN BISNIS ONLINE DI PEKANBARU - nelsi arisandy (Jurnal Ilmiah Ekonomi Dan Bisnis, 2017)
Abstract: The purpose of this study is to provide empirical evidence about the influence ofthe taxpayer understanding, awareness of taxpayers and sanction tax compliance with taxcompliance individual who doing business online activities in Pekanbaru. The type of thisresearch is quantitative. The population in this study is an individual taxpayer who live inPekanbaru. The sample in this study is an individual taxpayer who doing business onlineactivities.Total sample is 100 respondents.The method of this sample using conveniencesampling method. The techniques used in this research is multiple linear regression.Theresults of this research show that the partial understanding of the taxpayer does notinfluencesignificantly with individual taxpayer compliance, while awareness of taxpayers andsanction tax compliance have significantly affect with the individual taxpayers who doingbusiness online. And simultaneously, the understanding of the taxpayer, the taxpayerawareness and sanction tax compliance have significantly influence with individual taxpayerswho doing business online in Pekanbaru.Keywords: Understanding of the taxpayer, the taxpayer awareness, Sanctions Taxes,Taxpayer Compliance.